Element-for-Element Replacement? Beware! There Might Be a "No-Entry" Sign - Lotfipour-Saedi, Kazem (Meta, 2000)
AbstractVarious definitions have been offered for translation, each assuming a different orientation to the nature of meaning and language but all sharing the notion of replacement of one sort or another. The commonsensically perceived framework of translation operation is also basically founded upon the notion of replacement, mostly leading to the illusion that translation is just a matter of replacing SL elements by TL ones. But due to the uniqueness of each language system on the one hand and the non-isomorphic nature of the relationship between form and meaning across language on the other, this replacement operation faces challenging problems. This paper argues that there is no direct route in this operation and the replacement becomes possible only through the determination of the value of the elements to be replaced.